A New Control and Design of PEM Fuel Cell Powered Air Diffused Aeration System - Doaa M. Atia; Faten H. Fahmy; Ninet M. Ahmed; Hassen T. Dorrah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
Aeration of water by using PEM fuel cell power is not only a new application of the renewable energy, but also, it provides an affordable method to promote biodiversity in stagnant ponds and lakes. This paper presents a new design and control of PEM fuel cell powered by diffused air aeration system for a shrimp farm in Mersa Matruh in Egypt. Also Artificial intelligence (AI) techniques control is used to control the fuel cell output power by controlling input gases flow rate. Moreover the mathematical modeling and simulation of PEM fuel cell is introduced. A comparison study is applied between the performance of fuzzy logic control (FLC) and neural network control (NNC). The results show the effectiveness of NNC over FLC.